Recent Advances in Computational Optimization Results of the Workshop on Computational Optimization WCO 2017 - Fidanova, Stefka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Our everyday lives are practically unthinkable without optimization. We constantly try to minimize our effort and to maximize the reward or progress achieved. Many real-world and industrial problems arising in engineering, economics, medicine and other domains can be formulated as optimization tasks. This volume presents a comprehensive collection of extended contributions from the 2017 Workshop on Computational Optimization. Presenting recent advances in computational optimization, it addresses important concrete applications, e.g. the modeling of physical processes, wildfire modeling, modeling processes in chemical engineering, workforce planning, wireless access network topology, parameter settings for controlling various processes, berth allocation, identification of homogeneous domains, and quantum computing. The book shows how to develop algorithms for them based on new intelligent methods like evolutionary computations, ant colony optimization, constrain programming andothers.
Chapter 1. Contraction methods for correlation clustering: the order is important (Laszlo Aszal´os) -- Chapter 2. Optimisation of Preparedness and Response of Health services in major crises using the IMPRESS platform (Nina Dobrinkova) -- Chapter 3. The new approach for dynamic optimization with variability constraints (Pawel Drag) -- Chapter 4. Intercriteria Analisys of ACO Performance for Workforce Planning Problem (Olympia Roeva) etc.
Keywords: Computational intelligence; Artificial intelligence; Algorithms; Computational Intelligence; Artificial Intelligence; Algorithms